Computed tomographic characterization of adnexal masses - Gurung, Ayeshna; Shrestha, Suman Kumar (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To evaluate the computed tomographic scan features of benign and malignant adnexal masses. Methods: Retrospective descriptive study of CT scan features of adnexal masses were evaluated at Department of Radiology of Nobel Medical College from April to September 2020. Initial ultrasound or clinical diagnoses of adnexal masses were referred for the CT scan. Incidental adnexal findings on abdominal-pelvic CT scan performed for other diagnosis were also included.Descriptive parameters were calculated. Results: Total 46 cases were studied where mean age was 41.3 years with range 10-74 years. Most common age group with adnexal masses were in between 30 and 50 years (56.6%); 86% had benign features and rest were associated with either ascites (66%) or peritoneal deposits (13%). Complex cysts (60%) was the most common consistency with simple cyst (26%) followed by solid (6%). Amongst the benign neoplastic lesions most of them were dermoid cysts (35%). Conclusions: CT scan can be used as a supplementary diagnostic tool for cystic and solid componentcharacterization of adnexal masses and help in evaluation of the nature and extent of disease. Keywords: adnexal mass, computed tomography, simple cyst, complex cyst